Applying Culturally Relevant Teaching to Workshops—The Checklist - Cecilia E Suarez; John M Diaz; Laura E Valencia (EDIS)
As the diversity of Extension clientele continues to grow, Extension educators must consider new ways of supporting this population. In this new 2-page article, a follow-up to EDIS article AEC678, Culturally Responsive Teaching: A Framework for Educating Diverse Audience, the authors provide a checklist to serve as a guiding tool when planning workshops and to ensure that participants feel connected to, engaged with, and understood while working toward achieving workshop educational goals. Written by Cecilia E. Suarez, John M. Diaz, and Laura E. Valencia, and published by the UF/IFAS Department of Agricultural Education and Communication. https://edis.ifas.ufl.edu/wc351